Anti-leucine-rich glioma-inactivated 1 encephalitis revealed by a manic episode: insights from frontal lobe dysfunction in neuropsychiatry through neuropsychology and metabolic imaging. A case report - Porpiglia, Federica; Guillaume, Maxime; Bliaux, Evangeline; Psimaras, Dimitri; Decazes, Pierre; Guillin, Olivier; Rothärmel, Maud; Morin, Alexandre (Frontiers in Psychiatry, 2023)
Background: Anti-leucine-rich glioma-inactivated 1 (LGI1) encephalitis is a limbic encephalitis that rarely presents as an isolated psychiatric syndrome. Case presentation: A 70-year-old patient first presented with behavioral disorder including hyperactivity, euphoria, with disinhibition and accelerated speech associated with severe insomnia and cognitive disorder. A manic episode was diagnosed and he received various psychotropic medications with no improvement. Invesitgations were negative (MRI showed T2 aspecific hyperintensities with no hyperintensities in limbic regions and EEG was normal) He was transferred to a nursing home, with a diagnosis of neurodegenerative condition. Later, he was referred to our unit for further investigations. A cerebral 18F-FDG-PET revealed an association of frontal hypometabolism and temporal and striatum hypermetabolism and CSF analysis revealed slightly increased white blood cell counts. Plasmatic anti-LGI1 antibodies were detected. The patient was treated with intra-venous immunoglobulin (IvIg) but showed no improvement. Second-line treatment (a combination of rituximab and cyclophosmphamide) was then administered for a year, leading to an improvement of neuropsychiatric symptoms and normalization of metabolic impairment on 18F-FDG-PET. Conclusion: In this report, we describe a novel case of a patient withanti-LGI1 encephalitis with a predominant long-term psychiatric presentation. An atypical presentation (such as atypical psychiatric symptoms, neurocognitive disorder, hyponatremia) should prompt further investigations such as CSF analysis, considering that MRI and EEG may be normal. FDG-Pet might be of interest but few data are available in the literature. Early treatment of anti-LGI1 encephalitis is crucial for overall prognosis and may delay the development of dementia in some cases.